PENGARUH PEMAKAIAN KONTASEPSI HORMONAL TERHADAP BERAT BADAN,TENSI DAN KELUHAN - Florentina Kusyanti, Florentina Kusyanti (VISIKES, 2024)
The government program that has been launched to plan the desired number of children in a family, as well as to space them out and prevent pregnancies, is expected (WUS) that women of childbearing age who are married and have active sexual relations must use contraception appropriately. The aim of this program is to reduce MMR and IMR, and to meet the quality of family planning programs. Objective To determine the effect of hormonal contraception on blood pressure, weight, side effects in hormonal contraceptive participants at PMB in the Mertoyudan Community Health Center area. research methods with secondary data, the number of respondents was 200 people, the sampling technique was Purposive sampling, so that a sample of 139 people was selected, the analysis was tested using a univariate test with a frequency distribution to see the results of each variable, then obtained using simple linear regression. Results The age characteristics of the majority are between 20-44 years, The most common parity is that respondents have 2 children, The most common side effect of weight gain is maintaining weight, the majority's blood pressure remains constant, whereas for the regression test with an R test result of 10%, and a T test of 8.035 and a significance value of 0.000 which is smaller than 0.05, it can be interpreted that there is an influence.